Expanding the donor pool - Ramos, Emilio (2002)
The short-term success rate of cadaveric renal transplants has improved dramatically during the past decade. In 1990, one-year graft survival rates were about 70%; by 2000, they were greater than 90% (United States Renal Data System, 2001). Unfortunately, as transplantation has become more successful, the number of candidates seeking this treatment has risen even more dramatically. Based on Organ Procurement Transplant Network (OPTN) data as of January 11, 2002, the waiting time for a cadaveric renal transplant has grown to a mean of 422 d for patients with blood type AB and 1453 d for patients with blood type O. As of May 1, 2002, there were 51,978 individuals awaiting renal transplants in the United States. In 2001, there were 6081 cadaveric donors; more than 15% of those procured grafts were discarded (1), resulting in only 8201 renal transplants and 885 kidney-pancreas transplants; during that same year, there were 6514 living renal transplants performed in the United States. To deal with the widening gap between supply and demand of cadaveric organs for renal transplantation, efforts to expand the organ donor pool have received increased attention. In this regard, alternative approaches to traditional organ donor selection have been proposed (Table1). These measures may be beneficial in terms of increasing the number of donors and decreasing the waiting time. However, deviation from the standard method of cadaver donor selection is not without possible negative impact on graft survival. Despite the fact that these nontraditional or expanded criteria donors (ECD) are more expensive to obtain and use than ideal cadaveric renal transplantation, it is a less expensive alternative for renal replacement therapy than dialysis in the long run, even when the improved quality of life after transplantation is not considered (2). Thus, we will review the potential impact of the expansion of the organ donor pool on renal graft function and survival. In addition, we will also review the impact of newer approaches to living donor kidney transplantation.